Kerokan and Benefits Provided In Maintaining Health Level During Pandemic - Alfredo Aldo Eka Putra Tjundawan; Onny Priskila; Mellisa; Ferdinand; Suryawan Ang; Agus Sugiono (Institute of Computer Science (IOCS), 2022)
Scraping is one of the oldest traditional medical methods. Scraping is one of the Chinese Medicine Techniques. Scrapings are known and used in various regions of Asia. Scrapings are considered to have benefits for maintaining a healthy body, increasing immunity against disease, and preventing disease entry into the body. This study aimed to examine the benefits of scrapings on health in preventing disease, maintaining body stability, and curing illness. The benefits of this research are the development of science in the health sector. The research method used is a qualitative method with a literature study approach. The results showed that scrapings could increase antioxidants and boost the body's immune system as long as scrapings are carried out according to the correct principles and methods. Scraping has a good impact on maintaining the level of public health during a pandemic because, during a pandemic, access to health facilities is very much restricted, so alternative self-medication becomes an essential thing to do. It can be concluded that scraping is a treatment technique that deserves to be studied and applied to maintain health in everyday life.